Factors influencing the pregnancy outcome of intrauterine insemination and follow-up treatment - Xuan Huang; Qin Sun; Xu Tang; Meiling Li; Cheng Zhou; Xi Cheng; Bing Yao; Li Chen (Wolters Kluwer Medknow Publications, 2023)
Background: Many factors were reported associated with the pregnancy rate of intrauterine insemination (IUI), which played key role is still debated. Aims: The aim of this study was to explore related clinical pregnancy outcome factor in IUI cycles of non-male factor. Settings and Design: The clinical data of 1232 IUI cycles in 690 couples experiencing infertility who attended the Reproductive Center of Jinling Hospital between July 2015 and November 2021 were retrospectively analysed. Materials and Methods: Female and male age, body mass index (BMI), anti-Müllerian hormone (AMH), male semen parameters before and after wash, endometrial thickness (EMT), artificial insemination timing and ovarian stimulation (OS) protocols were compared between the pregnant group and the non-pregnant group in order to explore any correlation. Statistical Analysis Used: Continuous variables were analysed using independent-samples t-test, and Chi-square test was used for comparison of measurement data between the two groups. P <0.05 was considered statistical significance. Results: There were statistically significant differences in female AMH, EMT and duration of OS between the two groups. The AMH was higher in the pregnant group than in the non-pregnant group (P < 0.01), the stimulated days was significantly longer (P < 0.05) and EMT was significantly greater (P < 0.01) in the pregnant group than in the non-pregnant group. Further analysis showed that when patients with IUI had the following conditions: AMH > 4.5 ng/ml, EMT between 8 and 12 mm and letrozole + human menopausal gonadotropin stimulation with higher clinical pregnancy. However, there were no differences between the pregnant group and the non-pregnant group amongst the female and male age, BMI, hormones on baseline and day of human chorionic gonadotrophin, number of ovulated oocytes, sperm parameters before and after wash, treatment protocols and the timing of IUI (P > 0.05). Furthermore, there were 240 couples who not pregnant received one or more cycles of in vitro fertilisation/intracytoplasmic sperm injection/ pre-implantation genetic technology treatment, and another 182 couples forgo follow-up treatment. Conclusion: The results of the present study demonstrate that the clinical IUI pregnancy rate is correlated with the factors of female AMH, EMT and OS protocol; more studies and samples are necessary to evaluate whether other factors affect pregnancy rate.